2000
DOI: 10.1053/euje.2000.0002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis and Management of Thoracic Aortic Dissection and Intramural Haematoma: a Prospective Study of Advantages of Multiplane vs. Biplane Transoesophageal Echocardiography

Abstract: Aims:The purposes of this study were to compare the accuracy of multiplane vs. biplane transoesophageal echocardiography (TEE) in the diagnosis of aortic dissection and aortic intramural haematoma, and to test whether these techniques provide all the diagnostic information required to make management decisions. Methods and Results:Fifty-eight consecutive patients with clinically suspected aortic dissection were studied with multiplane TEE; all cases who required surgery underwent intraoperative monitoring with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…De modo geral, pode-se considerá-lo uma condição tão potencialmente catastrófica quanto a DAA e inferir que a mortalidade seja significativa -20 a 80% [114][115][116] , que a evolução para dissecção verdadeira deva ocorrer em 15 a 41% dos casos [117][118][119][120] , a ruptura em 5 a 26% dos pacientes, e a evolução para cura espontânea, de forma variável 121,122 . Em um levantamento prospectivo recente de 360 casos de dissecções aórticas agudas, Nienaber e cols.…”
Section: Recomendaçõesunclassified
“…De modo geral, pode-se considerá-lo uma condição tão potencialmente catastrófica quanto a DAA e inferir que a mortalidade seja significativa -20 a 80% [114][115][116] , que a evolução para dissecção verdadeira deva ocorrer em 15 a 41% dos casos [117][118][119][120] , a ruptura em 5 a 26% dos pacientes, e a evolução para cura espontânea, de forma variável 121,122 . Em um levantamento prospectivo recente de 360 casos de dissecções aórticas agudas, Nienaber e cols.…”
Section: Recomendaçõesunclassified
“…Generally, this can be considered a condition as potentially catastrophic as acute aortic dissections inferring that the mortality rate is significant -from 20 to 80% [110][111][112]; the evolution to true dissections occurs in 15 of 41% of the cases [112][113][114][115][116], to ruptures in 5% to 26% of the patients and evolution to spontaneous cure varies [117,118]. In a recent study of 360 cases of acute aortic dissections, Nienaber et al [113] observed that 25 (12%) cases presented evident false lumen, but without identified intimal injury in the diagnostic examinations.…”
Section: Cca -Cardiocirculatory Arrestmentioning
confidence: 99%
“…Recent studies suggest that less invasive studies such as TEE, CT scanning and MRI provide excellent diagnostic accuracy and mitigate some of the risks inherent to retrograde angiography (Table 2). [7][8][9][10][11][12][13][14][15][16][17][18][19] Unfortunately, the methodology of the research studies supporting the use of these alternative imaging modalities may make their results inappropriate for populations with a relatively low prevalence of aortic dissection.…”
Section: Discussionmentioning
confidence: 99%